RANCANG BANGUN APLIKASI SISTEM PAKAR BERBASIS PROGRESSIVE WEB APPS UNTUK REKOMENDASI PEMILIHAN PROGRAM STUDI - Rully Fildansyah (Universitas Nusa Cendana, 2021)
Having a high level of education is everyone's dream. Because with high education someone will have the competence and ability according to their field. The study program is something that someone must choose to study in college. Selection of a study program is an important first step, because it determines what will be studied in the future. However, in reality the decisions taken in choosing a study program often cause problems, as a result of the study program being taken only to follow friends or because of parental coercion and not according to their talents and interests. This causes many students to feel that they are wrong in their majors and find it difficult to study in the study program they have chosen and finally decide to change majors and even drop out of college. For this reason, an expert system application based on progressive web apps (PWA) was created that can provide recommendations for appropriate study programs and can help find out what intelligence the prospective student has based on the multiple intelligences theory popularized by Howard Gardner. The method used in making this expert system is the forward chaining method and the method of developing this expert system application uses the waterfall model System Development Life Cycle (SDLC) method.